Investigating the impact of abrasive tool wear on surface topography and microstructure evolution in polished GH4169G alloy through experiments and multi-scale simulations - Rui Yang; Xiaojun Lin; Youwei Chen; Tao Zhao (Journal of Materials Research and Technology)
This study investigates the influence of abrasive tool wear on the surface topography and microstructure evolution of GH4169G during polishing, combining experiments and simulations to assess surface functionality. Polishing experiments using abrasive cloth flap wheels (ACFW) with varying wear states were conducted, followed by 3D surface topography analysis and TEM observations of subsurface microstructures. Results show that blunt wear enhances liquid retention and load-bearing capacity while reducing directional texture, whereas fracture wear improves surface smoothness and wear resistance. As grits blunt, subsurface dislocation density increases, evolving from edge dislocations to dislocation entanglement, dislocation arrays, and dislocation walls. Grain fragmentation exhibits nonlinear variations, while grain boundary cracking probability decreases. These findings reveal the mechanisms of grit wear effects on surface functionality and microstructure evolution in GH4169G polishing.